Patients with suboptimal hepatitis B virus diagnostic characterization are at risk of liver fibrosis progression. Issue 3 (March 2020) - Morales-Arraez, Dalia; Diaz-Flores, Felicitas; Alonso, Ana; de Vera, Antonia; Jimenez, Alejandro; Garcia Dopico, Jose A.; Quintero, Enrique; Hernández-Guerra, Manuel
Abstract : Background: Many patients with chronic hepatitis B virus infection remain infradiagnosed and untreated. In a national health system with unrestricted access to treatment, our aims were to assess the level of compliance with clinical guidelines and the characteristics and risk of fibrosis progression in patients with suboptimal diagnosis. Methods: In a cohort of patients with positive hepatitis B surface antigen from January 2011 to December 2013, data were registered to assess characteristics and compliance with guidelines. For assessing the risk of liver fibrosis, positive hepatitis B surface antigen patients from January 2008 to December 2013 were grouped depending on DNA request. Liver fibrosis was estimated by serological scores. Results: Of 41 158 subjects with hepatitis B surface antigen request, 351 (0.9%) tested positive, and DNA was not available from 110 patients (66.4% male, mean 42.4 ± 14.5 years) after a median of 25.6 months (range 12.0–43.5). Most of these patients (76%) were assessed by primary care. Half of the patients (47.2%) showed hypertransaminasemia, at least significant fibrosis, or both conditions. After long follow-up (mean 90.1 ± 45.2 months), these patients had a higher risk of achieving at least significant fibrosis during follow-up (log-rank 8.73; P = 0.003). Conclusion: In more than one-third of patients with positive hepatitis B surface antigen, DNA was not requested despite showing hypertransaminasemia and significant fibrosis. Patients without DNA request are at high risk of liver fibrosis progression. Thus, educational measures and other strategies are necessary, especially targeting primary care, to improve access to treatment. Abstract : Supplemental Digital Content is available in the text.